The Effect of the Treatment with Heated Humidified High-Flow Nasal Cannula on Neonatal Respiratory Distress Syndrome in China: A Single-Center Experience - Ge Zheng; Xiao-qiu Huang; Hui-hui Zhao; Guo-Xing Jin; Bin Wang (Canadian Respiratory Journal)
Background. Noninvasive respiratory support is considered the optimal method of providing assistance to preterm babies with breathing problems, including nasal continuous positive airway pressure (NCPAP) and humidified high flow nasal cannula (HHHFNC). The evidence of the efficacy and safety of HHHFNC used as the primary respiratory support for respiratory distress syndrome (RDS) is insufficient in low- and middle-income countries. Objective. To investigate the effect of heated humidified high flow nasal cannula on neonatal respiratory distress syndrome compared with nasal continuous positive airway pressure. Methods. An observational cross-sectional study was performed at a tertiary neonatal intensive care unit in suburban Wenzhou, China, in the period between January 2014 and December 2015. Results. A total of 128 infants were enrolled in the study: 65 in the HHHFNC group and 63 in the NCPAP group. The respiratory support with HHHFNC was similar to that with NCPAP with regard to the primary outcome. There is no significant difference between two groups in secondary outcomes. Comparing with NCPAP group, the incidence of nasal damage was lower in HHHFNC group. Conclusions. HHHFNC is an effective and well-tolerated strategy as the primary treatment of mild to moderate RDS in preterm infants older than 28 weeks of GA.